2020
DOI: 10.1111/anu.13211
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on growth, survival and pigmentation ofSolea aegyptiacalarvae by using four different microalgal species with emphasize on water quality and nutritional value

Abstract: This study aimed to evaluate appropriate water sources to improve Solea aegyptiaca aquaculture from larval to the juvenile stage using two water sources (Eastern Harbour (EH) and MaxWell (MW)). Firstly, four microalgae's nutritional value (Nannochloropsis salina, N. oculata, Chlorella salina and Tetraselmis chuii) was assessed in both water sources. MW of high nitrate content enhanced the algal biomass and biochemical composition of all species compared to EH. MW-N. salina showed the highest growth and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…On the other hand, aquaculture is a promising industry that supplies essential and cheap animal protein to meet a growing world population [74,85]. Protein is considered the most important ingredients in aquaculture diets.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, aquaculture is a promising industry that supplies essential and cheap animal protein to meet a growing world population [74,85]. Protein is considered the most important ingredients in aquaculture diets.…”
Section: Discussionmentioning
confidence: 99%
“…In macroalgae, the lipids constitute a suitable storage material widely distributed, in different macroalgal classes ( Sudhakar et al, 2019 ). Lipid is a calorific component that can be used for aquaculture ( El‐Khodary et al, 2020 ) or feedstock for biodiesel ( Essa et al, 2018 ; Ashour et al, 2019 , Elshobary et al, 2019 , Huo et al, 2020 ). Despite the current study observed low lipid content (4.23 %DW), this is comparable with other reports, which showed the lipid content of macroalgae were<5% of dry weight ( Elshobary et al, 2020a , Khairy and El-Shafay, 2013 , Osman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effective application is the use of biostimulants in the form of mixtures of phytochemicals that could induce plant growth and yield while they improve protection against biotic and abiotic stresses, without any drawbacks [ 4 , 5 , 6 , 7 ]. Marine organisms are rich in phytochemical biomolecules with diverse biological activities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In this context, seaweeds would have been wielded as biostimulants [ 5 , 6 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%